2021
DOI: 10.32479/ijeep.10940
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Production, Energy Consumption and Capital Formation: Analyzing the Footprints in Indonesia

Abstract: We aim to investigate the effect of gross and fixed form of capital formation on electricity production and energy consumption in Indonesia during the period 1993-2018. Our found results are suggesting that most of the gross/fixed capital formation measures are not affecting either the electricity production or the energy production in Indonesia. However, more specifically key measures of gross/fixed capital formation like Gross fixed capital formation, private sector (% of GDP) and gross fixed capital formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Again, we can see similar findings in the study based on Balkan countries where the authors Mitić, Kostić [92] found that CO2 emissions and industrial fixed capital formation both have unidirectional causalities. The result from Pugu [93] suggested that electricity production and energy production in Indonesia are not affected by most measures of gross/fixed capital formation Adhikary [94] revealed that in Bangladesh, growth in real GDP is significantly influenced by FDI and capital formation. The author also stated that to enhance Bangladesh's economic growth rates, policymakers should formulate FDI-led policies and ensure higher levels of capital formation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Again, we can see similar findings in the study based on Balkan countries where the authors Mitić, Kostić [92] found that CO2 emissions and industrial fixed capital formation both have unidirectional causalities. The result from Pugu [93] suggested that electricity production and energy production in Indonesia are not affected by most measures of gross/fixed capital formation Adhikary [94] revealed that in Bangladesh, growth in real GDP is significantly influenced by FDI and capital formation. The author also stated that to enhance Bangladesh's economic growth rates, policymakers should formulate FDI-led policies and ensure higher levels of capital formation.…”
Section: Literature Reviewmentioning
confidence: 99%